2020
DOI: 10.1097/md.0000000000020033
|View full text |Cite
|
Sign up to set email alerts
|

Regional variation in states’ naloxone accessibility laws in association with opioid overdose death rates-Observational study (STROBE compliant)

Abstract: Though overall death from opioid overdose are increasing in the United States, the death rate in some states and population groups is stabilizing or even decreasing. Several states have enacted a Naloxone Accessibility Laws to increase naloxone availability as an opioid antidote. The extent to which these laws permit layperson distribution and possession varies. The aim of this study is to investigate differences in provisions of Naloxone Accessibility Laws by states mainly in the Northeast and West regions, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Increased access to naloxone at the state and community level is associated with reduced risk for death from overdose, and, consequently, widespread availability is recommended. [14][15][16][17] Statewide real-time pharmacy availability of naloxone-as patients would experience availability-has not been previously reported. These findings suggest unpredictable same-day availability that may affect experience and care outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Increased access to naloxone at the state and community level is associated with reduced risk for death from overdose, and, consequently, widespread availability is recommended. [14][15][16][17] Statewide real-time pharmacy availability of naloxone-as patients would experience availability-has not been previously reported. These findings suggest unpredictable same-day availability that may affect experience and care outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…7 Despite advancements in easing legal restrictions on naloxone distribution to expand mechanisms for people to access this medication, studies have demonstrated mixed effectiveness of NALs in reducing opioid overdose deaths. [7][8][9] A recent systematic review found no associations between state-level NALs and opioid overdose deaths in more recent years (2015-2016) compared to earlier analyses where significant protective effects were found. 7 These results suggest that policy change alone may not be enough to achieve widespread naloxone possession among people likely to witness or experience an opioid overdose.…”
Section: Introductionmentioning
confidence: 95%
“…Because naloxone is a prescription medication and not available over-the-counter (OTC), the implementation of community naloxone distribution programs has relied on state-level naloxone access laws (NALs), which vary by state 7 . Despite advancements in easing legal restrictions on naloxone distribution to expand mechanisms for people to access this medication, studies have demonstrated mixed effectiveness of NALs in reducing opioid overdose deaths 7 9 . A recent systematic review found no associations between state-level NALs and opioid overdose deaths in more recent years (2015–2016) compared to earlier analyses where significant protective effects were found 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Underutilization of naloxone may be in part due to stigma over its possession, lack of availability, as well as variability among state laws regarding layperson distribution [11][12][13]. In states in which naloxone availability is mandated at pharmacies, it has been found that locations in neighborhoods with lower socioeconomic status reported either lower quantity or no stock at all, potentially contributing to a lack of access in these environments [12].…”
Section: Introductionmentioning
confidence: 99%